Review on clinical management involving post-partum diseases in ruminants - Abdullah, Faez Firdaus Jesse (Nexus Academic Publishers, 2019)
The major aim of animal husbandry is to maximise production but over time reproductive problems have always contributed negatively thereby resulting to economic downturn to farmers. Reproductive disorders among livestock production animals such as buffaloes, cattle, sheep and goats are of major concern hence needed to be emphasized the more. These disorders have always lead to loss in fertility. The obstetrical problem was found to be the highest prevalence in clinical cases of genital tract and the major factor that renders the reproductive performance to be at low border is post-partum diseases. Post-partum being defined as duration right after parturition and the stages initially start on the second stage of parturition which is the expulsion of the foetus, followed by expulsion of the placenta. The occurrence of clinical cases of post-partum diseases can be tapered down by instantaneous treatment and clinical management by the veterinarians. The common post-partum conditions in ruminants are haemorrhage, retained placenta or retained foetal membrane (RFM), genital (uterine and vaginal) prolapsed, genital tears and uterine infections (metritis, endometritis, pyometritis). These conditions may influence the productive performances of the affected ruminants such as length of oestrous cycle, calving interval, service per concept, calving to first oestrous and service period. There is a limited review on clinical management of post-partum diseases involving ruminants. Hence, this review focused on the clinical management of common post-partum diseases involving ruminants. Therefore, this review may enlighten the field veterinarians on the common post-partum diseases of small and large ruminants and its clinical management.